2020
DOI: 10.1029/2020gl087499
|View full text |Cite
|
Sign up to set email alerts
|

Two Layers of Melting Ice Particles Within a Single Radar Bright Band: Interpretation and Implications

Abstract: Dual‐frequency dual‐polarization radar observations of the melting of two ice populations in a stratiform rainfall event are presented. The observed phenomenon occurs as a two‐layer linear depolarization ratio (LDR) signature in a single radar bright band. Doppler spectra observations show that the upper LDR layer is caused by the melting of ice needles, potentially generated by the rime‐splintering process, while the lower one is mainly due to the melting of background ice particles formed at the cloud top. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 63 publications
(100 reference statements)
5
33
0
Order By: Relevance
“…We note that because the R CB retrievals, described by the third moment of the size distribution (IWC) weighted by V D , are based on radar reflectivity measurements (sixth moment), the uncertainties associated with the resultant R CB values are likely to be smaller than in equivalent Z e -based retrievals of ice crystal number concentration (zeroth moment) (see Ulbrich, 1983). The Arctic and Antarctic sites represent relatively contrasting polar conditions, with a drier, colder, and more pristine atmosphere over McMurdo Station (e.g., Bromwich et al, 2012;Lubin et al, 2020;Shupe et al, 2011;Silber et al, 2018a). Despite these atmospheric state differences between the two sites, the general similarity of Arctic and Antarctic precipitation occurrence reported here at cloud base strongly suggests that they are regionally representative at least to some degree.…”
Section: Guidance For Large-scale Modelsmentioning
confidence: 57%
See 2 more Smart Citations
“…We note that because the R CB retrievals, described by the third moment of the size distribution (IWC) weighted by V D , are based on radar reflectivity measurements (sixth moment), the uncertainties associated with the resultant R CB values are likely to be smaller than in equivalent Z e -based retrievals of ice crystal number concentration (zeroth moment) (see Ulbrich, 1983). The Arctic and Antarctic sites represent relatively contrasting polar conditions, with a drier, colder, and more pristine atmosphere over McMurdo Station (e.g., Bromwich et al, 2012;Lubin et al, 2020;Shupe et al, 2011;Silber et al, 2018a). Despite these atmospheric state differences between the two sites, the general similarity of Arctic and Antarctic precipitation occurrence reported here at cloud base strongly suggests that they are regionally representative at least to some degree.…”
Section: Guidance For Large-scale Modelsmentioning
confidence: 57%
“…To detect supercooled cloud layers, we use 6 or 12 hourly soundings acquired at Utqiaġvik (formerly Barrow), North Slope of Alaska (NSA; Verlinde et al, 2016), from November 2011 to April 2019 and 12 hourly soundings acquired at McMurdo Station, Antarctica, between December 2015 and January 2017 (Lubin et al, 2020). After linearly interpolating onto a 15 m grid, supercooled layers are identified where atmospheric temperature is between 0 and −40 • C and relative humidity (RH) exceeds 95 % over at least two adjacent grid cells, consistent with an RH uncertainty of 5 % (Holdridge et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SKYLER, like a typical centimeter wavelength radar, observed a bright band marked by clear boundaries at both the top and the bottom. Inferring information about the ice-melting process from the properties of the radar-detected bright band is still an active area of research (e.g., Heymsfield et al, 2015;Li et al, 2020). The early work of Fabry and Zawadzki (1995) suggested that the magnitude and vertical extent of the radar reflectivity enhancement at centimeter-wavelength radars are influenced by precipitation rate, phase transitions (i.e., liquid coating ice), change in fall speed throughout melting, precipitation growth and changes in the particle size distribution linked to aggregation and breakup.…”
Section: Using G-band For Characterizing Melting and Sizing Sub-millimeter Drizzle Dropletsmentioning
confidence: 99%
“…Riming is an important snow growth process and has an impact on the physical properties of ice particles (Barthazy & Schefold, 2006; Erfani & Mitchell, 2016; Grazioli et al., 2015; Li et al., 2018; Moisseev et al., 2017). Riming can also impact the microphysical properties of the melting layer (Li & Moisseev, 2020; Li et al., 2020; Mroz et al., 2020) and rainfall below the melting layer (Lin et al., 2020; Sarma et al., 2016). Furthermore, riming is affected by anthropogenic aerosols (Borys et al., 2003; Jackson et al., 2012), which is also supported by the ECHAM4 general circulation model simulations (Lohmann, 2004).…”
Section: Introductionmentioning
confidence: 99%